The Theoretical Individual Imagination, Ethics and the Future of Humanity - Tobias, Michael Charles (Springer International Publishing, 2018)
How can the one influence the many? From posing seminal questions about what comprises a human individual, to asking whether human evolution is alive and well, favoring individuals or the species, this work is a daring, up-to-the-minute overview of an urgent, multidisciplinary premise. It explores the extent to which human history provides empirical evidence for the capacity of an individual to exert meaningful suasion over their species, and asks: Can an individual influence the survival of the human species and the planet? If there are to be cultures of transformation dedicated to seeing us all through the Sixth Extinction Spasm, the Anthropocene, inflicting as little biological havoc as possible, what might such orientations-a collective, widespread biophilia, or reverence for nature-look like? In this powerful work, with a combination of data and direct observation, the authors invite readers to explore how such transformations might resonate throughout the human community; in what ways a person might overcome the seemingly insurmountable environmental tumult our species has unleashed; the clear and salient motives, ethics, aspirations and pragmatic idealism he/she might mirror and embrace in order to effect a profound difference-at the individual level-for all of life and life's myriad habitats. Chapters illuminate an ambitiously broad digest of research from two-dozen disciplines. Those include ecodynamics, biosemiotics, neural plasticity, anthropology, paleontology and the history of science, among others. All converge upon a set of ethics-based scenarios for mitigating ecological damage to ourselves and other life forms. This highly readable and tightly woven treatise speaks to scientists, students and all those who are concerned about ethical activism and the future of the biosphere. Michael Charles Tobias and Jane Gray Morrison are ecological philosophers and animal liberation activists who have worked for decades to help enrich our understanding of ecosystem dynamics and humanity's ambiguous presence amid that great orchestra that is nature.